Vasculitogenic T Cells in Large Vessel Vasculitis - Watanabe, Ryu; Hashimoto, Motomu (Frontiers in Immunology, 2022)
Vasculitis is an autoimmune disease of unknown etiology that causes inflammation of the blood vessels. Large vessel vasculitis is classified as either giant cell arteritis (GCA), which occurs exclusively in the elderly, or Takayasu arteritis (TAK), which mainly affects young women. Various cell types are involved in the pathogenesis of large vessel vasculitis. Among these, dendritic cells located between the adventitia and the media initiate the inflammatory cascade as antigen-presenting cells, followed by activation of macrophages and T cells contributing to vessel wall destruction. In both diseases, naive CD4+ T cells are polarized to differentiate into Th1 or Th17 cells, whereas differentiation into regulatory T cells, which suppress vascular inflammation, is inhibited. Skewed T cell differentiation is the result of aberrant intracellular signaling, such as the mechanistic target of rapamycin (mTOR) or the Janus kinase signal transducer and activator of transcription (JAK-STAT) pathways. It has also become clear that tissue niches in the vasculature fuel activated T cells and maintain tissue-resident memory T cells. In this review, we outline the most recent understanding of the pathophysiology of large vessel vasculitis. Then, we provide a summary of skewed T cell differentiation in the vasculature and peripheral blood. Finally, new therapeutic strategies for correcting skewed T cell differentiation as well as aberrant intracellular signaling are discussed.